Issue Information. (April 2017) - Unknown
Abstract : Front cover: Today, more than one fourth of people living in Japan are estimated to be suffering from 'sugi' or Japanese cedar ( Cryptomeria japonica ) pollinosis. Spring should be the worst season for those with such allergies. Binding of the allergen to immunoglobulin E (IgE) on the surface of mast cells triggers release of histamine from them, and it causes symptoms such as itchy eyes or snivel. However, it's not a problem only for human beings. This monkey performing saru‐mawashi (monkey show) also has a pollen allergy, and today's stage is, of all places, beside the very sugi tree! Designed by TRAIS Co., Ltd. (Kobe, Japan).